Comparison of outcomes between off-pump versus on-pump coronary artery bypass surgery in elderly patients: a meta-analysis - Zhu,Z.G. (2017)
The aim of this study was to analyze if off-pump coronary artery bypass surgery (CABG) is associated with better treatment outcomes in elderly patients (>70 years of age) than on-pump CABG, using meta-analysis. Medline, PubMed, Cochrane and Google Scholar databases were searched until September 13, 2016. Sensitivity and quality assessment were performed. Twenty-two studies, three randomized control trials (RCTs) and 20 non-RCTs were included with 24,127 patients. The risk of death associated with on-pump or off-pump CABG in the RCTs were similar (pooled OR=0.945, 95%CI=0.652 to 1.371, P=0.766). However, in the non-RCTs, mortality risk was lower in patients treated with off-pump CABG than on-pump CABG (pooled OR=0.631, 95%CI=0.587 to 0.944, P=0.003). No differences were observed between the two treatment groups in terms of the occurrence of 30-day post-operative stroke or myocardial infarction (P≥0.147). In the non-RCTs, off-pump CABG treatment was associated with a shorter length of hospital stay (pooled standardized difference in means=-0.401, 95%CI=-0.621 to -0.181, P≤0.001). The meta-analysis with pooled data from non-RCTs, but not RCTs, found that mortality was lower with off-pump compared with on-pump CABG, and suggested that there may be some benefit of off-pump CABG compared with on-pump CABG in the risk of mortality and length of hospital stay.